2013
DOI: 10.1007/978-3-7091-1511-4_5
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer and Lung Injury: The Dual Role of Ceramide

Abstract: Sphingolipids play key roles in cancer, yet our current understanding of sphingolipid function in lung cancer is limited to a few key players. The best characterized of these are sphingosine-1-phoshate and ceramide which are described for their opposing roles in cell fate. However, because sphingolipids as a whole are readily interconverted by a complex enzymatic machinery, no single sphingolipid appears to have exactly one role. Instead, the roles of specific sphingolipids appear to be context specific as dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 89 publications
2
35
0
1
Order By: Relevance
“…Modulators of mRNA expression of telomerase components (hTERT) have been regarded as one of type of anti telomeral agents. These include all transretonoic acid (Xiao et al, 2005), 5, 6-trans-16 -ene vitamin D3 (Holysz et al, 2013) ceramide (Goldkom et al, 2013) and curcumin (Kazemi et al, 2011). These complexes act as inhibitors of hTERT mRNA expression which results in decreased telomerase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Modulators of mRNA expression of telomerase components (hTERT) have been regarded as one of type of anti telomeral agents. These include all transretonoic acid (Xiao et al, 2005), 5, 6-trans-16 -ene vitamin D3 (Holysz et al, 2013) ceramide (Goldkom et al, 2013) and curcumin (Kazemi et al, 2011). These complexes act as inhibitors of hTERT mRNA expression which results in decreased telomerase activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent evidence has demonstrated that the roles of ceramide are concentration, cell context, and subcellular localization specific [8,9,[28][29][30]. For example, C16 ceramide is shown to favor cancer cell proliferation and promote metastasis in lung cancer patients with CerS6 elevation [28,29,[31][32][33].…”
Section: Ceramide and Related Enzymes In Lung Cancer Pathologymentioning
confidence: 99%
“…Ceramide has been linked to cigarette smoking, the number one risk factor for lung cancer [8,9,34,35]. Higher ceramide levels are reported in emphysema patients who are smokers, a subpopulation of patients greatly susceptible to lung cancer [34].…”
Section: Ceramide and Related Enzymes In Lung Cancer Pathologymentioning
confidence: 99%
See 2 more Smart Citations